Methods: Increasing feasibility of total blood cell count analysis in field studies: Effects of plastic tubes and storage duration - Janča, Matouš; Knotková, Zora; Kauzál, Ondřej; Albrecht, Tomáš; Tomášek, Oldřich (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2025)
Total red (RBC) and white (WBC) blood cell counts are highly informative haematological parameters, holding substantial potential for advancing ecological and evolutionary research and conservation efforts. Yet, their use in studies on wild bird populations is rare as blood samples need to be stored in fragile glass flasks and analysed on the day of collection, which poses significant challenges in field conditions. Here, we aimed to make total blood cell counts more accessible for field studies by assessing their reliability in blood samples collected in more durable plastic tubes and stored for varying periods of time. We used the zebra finch (Taeniopygia castanotis) as a model and aliquoted the collected blood samples into plastic tubes and glass flasks with Natt-Herrick's staining solution. When analysed on the day of collection, total RBC and WBC counts from the plastic tubes and glass flasks showed no difference and were highly repeatable. A subsequent repeated analysis of samples stored at 4–8 °C in plastic tubes for 18 months showed moderate repeatabilities of resultant blood cell counts that did not decrease over time. Together with the absence of linear trends in the results, consistent repeatabilities indicate that the total blood cell count information is effectively preserved in the long term. Overall, our study shows that blood samples can be collected in plastic tubes with Natt-Herrick's solution for analysis of total RBC and WBC counts. Moreover, long-term sample storage can be a viable option when immediate cell count analysis is impracticable, such as in field studies requiring sampling in remote locations. However, the moderate repeatability of cell counts in stored samples must be considered, particularly in within-population studies where relatively low biological variation is expected, which may require high analytical precision. These findings may facilitate more extensive application of total blood cell counts in wild bird research and conservation. [Display omitted] •Plastic tubes do not affect total RBC and WBC counts, supporting their use as a glassware alternative.•Long-term blood storage in plastic tubes with Natt-Herrick's solution preserves cell counts, though with reduced precision.•Long-term storage of blood in plastic tubes may facilitate the use of total blood cell counts in field studies.